Inhibition of DNA methyltransferase stimulates the expression of signal transducer and activator of transcription 1, 2, and 3 genes in colon tumor cells - Karpf, Adam R. (National Academy of Sciences, 1999)
Inhibitors of DNA methyltransferase, typified by 5-aza-2′-deoxycytidine (5-Aza-CdR), induce the expression of genes transcriptionally down-regulated by de novo methylation in tumor cells. We utilized gene expression microarrays to examine the effects of 5-Aza-CdR treatment in HT29 colon adenocarcinoma cells. This analysis revealed the induction of a set of genes that implicated IFN signaling in the HT29 cellular response to 5-Aza-CdR. Subsequent investigations revealed that the induction of this gene set correlates with the induction of signal transducer and activator of transcription (STAT) 1, 2, and 3 genes and their activation by endogenous IFN-α. These observations implicate the induction of the IFN-response pathway as a major cellular response to 5-Aza-CdR and suggests that the expression of STATs 1, 2, and 3 can be regulated by DNA methylation. Consistent with STAT’s limiting cell responsiveness to IFN, we found that 5-Aza-CdR treatment sensitized HT29 cells to growth inhibition by exogenous IFN-α2a, indicating that 5-Aza-CdR should be investigated as a potentiator of IFN responsiveness in certain IFN-resistant tumors.